The guardians of capitalism: International consensus and fascist technocratic implementation of austerity - Clara Elisabetta Mattei (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
Current debates on austerity often forget that these policies are almost 100 years old .This paper explores how the combination of austerity and technocracy acted as a powerful tool to secure the compliance of European countries to socio-economic stabilization after WWI. Austerity emerged as an economic, moral and technocratic message as economic experts sought to educate the restless post-war civil society. This paper analyses primary austerity documents from the international economic conferences of Brussels (1920) and Genoa (1922). In addition I use a case study of Italy (1922-1925) to show how austerity succeeded under the first years of Fascism, when the government authorized prominent economics professors to implement the international financial codes devised at Brussels and Genoa. This essay considers the scientific writings of De Stefani, Ricci and Pantaleoni to examine the theoretical roots of the technocratic nature of austerity.
Keywords: N14; N44; B41; 330; Austerity; Technocracy; Post-WWI Financial Conferences; Economists as Consultants; Fascism